Spatial Distribution of Immune Cells in Head and Neck Squamous Cell Carcinomas - Idel, Christian; Ribbat-Idel, Julika; Klapper, Luise; Krupar, Rosemarie; Bruchhage, Karl-Ludwig; Dreyer, Eva; Rades, Dirk; Polasky, Christina; Offermann, Anne; Kirfel, Jutta; Perner, Sven; Wollenberg, Barbara (Frontiers in Oncology, 2021)
Background Head and neck squamous cell carcinomas (HNSCCs) have a very moderate response rate to immune checkpoint inhibitor (ICI) treatment compared to other cancer types. Lacking predictive markers for treatment response, we analyzed the immune status of HNSCC and assessed the spatial distribution of immune cells. Materials and Methods Via assessing hematoxylin–eosin (H&E) stains, we divided HNSCCs by the immune cell distribution in hot, cold, and excluded tumors. For each group, each with 10 tumors, we performed serial immunohistochemical (IHC) staining of the immune cell markers, checkpoint molecules, and immune regulators. Results The spatial distributions were different for each immune cell type, allocating regulatory T cells (Tregs) and CD11b cells predominantly in the stroma. CD4 and CD8 cells were present either in the tumor stroma or between cancer cells. Interestingly, the expressions of PD-1 (programmed cell death 1 receptor) and PD-L1 (programmed death-ligand 1) were higher in hot tumors in comparison to cold and excluded tumors. The expression of pSMAD [indicating active transforming growth factor beta (TGF-β)] was higher in excluded tumors. Conclusion Different immune cell distribution patterns within tumors might be crucial for ICI treatment response since hot tumors have the highest expressions of PD-1 and PD-L1. TGF-β might be a key regulator for immune cell distribution and a promising therapeutic target that determines the formation of hot or excluded immune patterns.